Effect of resistance training on liver fat and visceral adiposity in adults with obesity: A randomized controlled trial. Issue 7 (18th September 2016) - Keating, Shelley E.; Hackett, Daniel A.; Parker, Helen M.; Way, Kimberley L.; O'Connor, Helen T.; Sainsbury, Amanda; Baker, Michael K.; Chuter, Vivienne H.; Caterson, Ian D.; George, Jacob; Johnson, Nathan A.
Abstract : Aim: Regular aerobic exercise reduces visceral adipose tissue (VAT) and liver fat, however, not all individuals are able to adopt and adhere to such programs. Progressive resistance training (PRT) may be an alternative therapy, but there is limited available evidence. We examined the efficacy of PRT as per current exercise guidelines, compared with sham exercise placebo on liver fat and VAT. Methods: Twenty‐nine inactive and overweight/obese (body mass index ≥25 kg/m 2 ) adults (age 29–59) were randomized to receive 8 weeks of PRT ( n  = 15, 10 exercises per session, 8–12 repetitions, 2–3 sets per exercise at 80–85% of one‐repetition maximum, 3 days per week) or a sham exercise placebo control (CON) ( n  = 14). Change in liver fat, VAT, and abdominal s.c. adipose tissue (SAT) were assessed by magnetic resonance spectroscopy and imaging). Results: There were no significant group by time interactions for change in liver fat in PRT versus CON groups (−0.07 ± 0.31% vs. 0.55 ± 0.77%, respectively, P  = 0.19), VAT (−175 ± 85 cm 3 vs. 10 ± 64 cm 3, respectively, P  = 0.11), or abdominal SAT (−436 ± 245 cm 3 vs. 127.29 ± 182 cm 3, respectively, P  = 0.10) despite a significant increase in muscle volume (55 ± 78 cm 3 vs. −0.04 ± 8 cm 3, respectively, P  = 0.03). Conclusion: Traditional PRT is not effective for reducing liver fat in overweight/obese adults compared with placebo control. Although PRT has known metabolic benefits, an adequate volume of aerobic exercise should be promoted if liver fat is the therapeutic target.